Phase transition in Cs₃Bi₂I₉ ferroelastic: investigation by Raman scattering technique - Motsnyi, F.V.; Vuychik, M.V.; Smolanka, O.M.; Peresh, E.Yu. (Functional Materials, 2005)
Raman scattering in unpolarized light has been studied for the first time for Cs₃Bi₂I₉ layered ferroelastic at temperatures from 5 to 300 К in the heating mode. Neither soft mode nor frequency softening was observed. For the low-frequency lines 37.0, 45.0, 61.4, 68.3 and 97.4 cm⁻¹, the doublets were detected. Those may be due to Davydov splitting or splitting of degenerate vibrations of E-symmetry. The intensity equalization effect has been found for 114.8 and 125.3 cm⁻¹ lines in the phase transition region. It is shown that the 150.6 and 131.2 cm⁻¹ lines can be explained by vibrations of Bi⁻¹ bonds in the [Bi1]³⁻ octahedrons. The Raman spectra in z(y,y)z and z(y,x)z polarizations taken at 100 К were found to be similar to those in unpolarized light. An analysis of both known and our results enabled us to conclude that the ferroelastic phase transition at Тᶜ = 220 К belongs to those of the first order but close to the second one. Впервые в неполяризованном свете изучено комбинационное рассеяние (КР) в слоистом сегнетоэластике Cs₃Bi₂I₉ при температурах 5-300 К в режиме нагревания. Не обнаружено ни мягкой моды, ни смягчения частот. 3арегистрированы дублеты у низкочастотных линий 37,0, 45,0, 61,4, 68,3 и 97,4 см⁻¹, обусловленных давыдовским расщеплением, либо расщеплением вырожденных колебаний симметрии Е. Обнаружен эффект выравнивания интенсивностей линий 114,8 и 125,3 см⁻¹ в области фазового перехода. Показано, что линии 150,6 и 131,2 см-1 можно объяснить колебаниями связей Bi⁻¹ в октаэдрах [Bi1 ]³⁻. Установлено, что при 100 К спектры КР в поляризации света z(y,y)z и z(y,x)z подобны спектрам КР в неполяризованном свете. На основе анализа известных и полученных нами данных сделан вывод о принадлежности сегнетоэластичного фазового перехода при Тᶜ = 220 К к фазовым переходам первого рода, близких ко второму. Вперше у неполяризованому свiтлi вивчено комбiнацiйне розсiювання (КР) у шаруватому сегнетоеластику Cs₃Bi₂I₉ при температурах 5-300 К у режимi нагрiвання. Не виявлено анi м'якої моди, анi пом'якшення частот. 3ареєстровано дублети у низькочастотних лiнiй 37,0, 45,0, 61,4, 68,3 i 97,4 см⁻¹, обумовлених давидiвським розщепленням, або ж розщепленням вироджених коливань симетрiї Е. Виявлено ефект вирiвнювання iнтенсивностей лiнiй 114,8 i 125,3 см⁻¹ в областi фазового переходу. Показано, що лiнii 150,6 i 131,2 см⁻¹ можна пояснити коливаннями зв'язкiв Bi⁻¹ в октаедрах [Bi16]³⁻. Встановлено, що при 100 К спектри КР у поляризацii свiтла z(y,y)z та z(y,x)z є подiбними до спектрiв КР у неполяризованому свiтлi. Проаналiзовано вiдомi та отриманi нами данi i зроблено висновок про належнiсть сегнетоеластичного фазового переходу при Тᶜ = 220 К до фазових переходiв першого роду, що є близькими до другого.